2019
DOI: 10.1523/eneuro.0044-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Drinking Slows Brain Development in Adolescent and Young Adult Nonhuman Primates

Abstract: The transition from adolescence to adulthood is associated with brain remodeling in the final stages of developmental growth. It is also a period when a large proportion of this age group engages in binge alcohol drinking (occasional consumption of four to five drinks leading to intoxication) and heavy alcohol drinking (binge drinking on ≥5 d in a month). Here we report on magnetic resonance imaging of developmental changes in the brain occurring during late adolescence and early adulthood (3.5–7.5 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…In contrast, lower DCX quantification in the DG has been reported in comparison to the controls in adult mice prenatally exposed to ethanol [ 48 ]. Increased signaling in immature neurons during fetal life may indicate a delay in the maturation processes produced by the oxidative damage generated by PAE on the organogenesis processes [ 49 , 50 ]. As for the effect of EGCG therapy in fetal neurogenesis, our results show an improvement in maturation and differentiation processes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lower DCX quantification in the DG has been reported in comparison to the controls in adult mice prenatally exposed to ethanol [ 48 ]. Increased signaling in immature neurons during fetal life may indicate a delay in the maturation processes produced by the oxidative damage generated by PAE on the organogenesis processes [ 49 , 50 ]. As for the effect of EGCG therapy in fetal neurogenesis, our results show an improvement in maturation and differentiation processes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, rhesus macaques were imaged before and after one year of alcohol exposure. Findings showed that brain volume increased in controls throughout adolescence into early adulthood; however, heavy drinking macaques showed reduced rates of brain growth over the follow-up period, particularly in white matter regions and the thalamus, in a dose-dependent fashion (115). These structural changes may be associated with cognitive aberrations continuing into adulthood.…”
Section: Comparable Cross-species Findingsmentioning
confidence: 96%
“…The INIA19 brain atlas ( Rohlfing et al, 2012 ) provides a template image of the mature rhesus macaque brain. In a recent study that characterized brain size changes from late adolescence through middle-aged adulthood in 71 (13 female) rhesus macaques ( Shnitko et al, 2019 ), the set of the 6 brain regions analyzed above were delineated on the INIA19 atlas. The volumes of these brain structures derived from the INIA19 template were found to be representative of the volume for each structure in the mature rhesus macaque.…”
Section: Resultsmentioning
confidence: 99%